Neonatal attendance at paediatric accident and emergency department, is it preventable?. (29th September 2015) - Hateley, C; Godambe, S; Salter, R; Chow, P
Abstract : Most neonatal discharges from postnatal ward occur within 48 h of birth with continuing support from the community. It is unclear how often these neonates would present in paediatric accident and emergency (A&E) department after discharge and the reasons for their attendance. Aim/Objective: To determine the incidence and diagnosis of neonates presenting to an inner city paediatric A&E department. To identify the route of referral of these neonates presenting at the paediatric A&E Methods: Retrospective audit of all neonates attending paediatric A&E between 1 January and 31 May 2008. Main outcome measures: age at presentation (days), sex, ethnicity, presenting complaint, referral route, diagnosis and destination after consultation. Results: Attendance to the paediatric A&E over this period was 8675. Of these, 117 were neonates (1.3%). The mean age at presentation was 13 days (range 0.06–28). Twenty-one (18%) presented with jaundice, 20% with vomiting and 10% with crying. Forty (34%) neonates were deemed to be well requiring reassurance only and 13 (11%) had feeding difficulties. Of the 21 neonates presented with jaundice, five required admission (ranged from 3–10 days at presentation). 59% of neonates presenting to the paediatric A&E had primary care type of problems. 77% neonates were sent home and only 23% was admitted to the paediatric ward. Black/Black British African neonates were more likely to attend than other ethnicities as they were over-represented in the data when comparing to the health authority statistics. 69% of referrals for jaundice were by health visitors, midwives and general practitioners, all of whom were discharged home. Conclusions: Majority of healthy neonates presenting at paediatric A&E did not require hospital admission. Support of feeding before and after discharge and developing care pathway programme in managing jaundice neonates in the community may reduce unnecessary paediatric A&E attendance in this group of neonates.